2020
DOI: 10.1021/acsanm.0c00444
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Composition of FeCo Nanoparticle Heating Agents for Magnetically Induced Catalysis

Abstract: Magnetic heating by nanoparticles has recently been successfully employed in heterogeneous catalysis. In such processes, the maximum temperature that can be reached depends on the Curie temperature (T c) of the heating material. Here, in order to extend the range of accessible temperatures and consequently the range of possible reactions, to those requiring high temperatures, we developed and fully characterized a series of FeCo nanoparticles containing different concentrations of cobalt, in order to tune thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 46 publications
6
70
0
Order By: Relevance
“…Thus, FeNi3 NPs which display low magnetocrystalline anisotropy, catalyze the CO2 hydrogenation at lower magnetic field than previously reported materials, e.g. FeC 35 and FeCo NPs, 43 thus improving the energy efficiency of the process. 48 Furthermore, FeNi3…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, FeNi3 NPs which display low magnetocrystalline anisotropy, catalyze the CO2 hydrogenation at lower magnetic field than previously reported materials, e.g. FeC 35 and FeCo NPs, 43 thus improving the energy efficiency of the process. 48 Furthermore, FeNi3…”
Section: Introductionmentioning
confidence: 82%
“…32 More recently, magnetic heating has also been applied to activate catalytic reactions as it permits generating a rapid and localized rise of the temperature at the surface of the heating agents without the need to heat up the whole reactor. Several groups including ours, explored the magnetic activation of heterogeneous catalytic reactions in the gas phase such as the Fischer-Tropsch reaction, 33,34 CO2 hydrogenation, [35][36][37][38][39] methane reforming [40][41][42][43] or alkane dehydrogenation. 43 Magnetic heating has also been used in liquid phase reactions, but it was often limited to reactions taking place at moderate temperatures such as C-C coupling, 44 amide condensation, 45 and more recently hydrogenation of furfural.…”
Section: Introductionmentioning
confidence: 99%
“…27 Their size, shape and chemical composition could be tuned by the experimental parameters (nature and concentration of ligands, precursor concentrations). 27,28 As prepared, these NPs exhibited saturation magnetization values comparable with the bulk one (Ms = 226 A.m².kg -1 ). 27,29 In this paper, we report the synthesis and the advanced magnetic characterization of FeCo nanooctopods.…”
Section: Introductionmentioning
confidence: 86%
“…Elsewhere, Das et al reported on the enhanced heating efficiency of elongated magnetic nanoparticles using the AC field [139], where they showed the shape anisotropy induced by elongation is the key for tuning the heating efficiency of the magnetic nanoparticles. The requirement of a high heating generation rate for special applications, such as nanowarming of cryopreserved organs, the AC field technique became a strong technique for characterizing the magnetic nanowires, as they are capable to generate much higher heats granted to their shape anisotropy [137,153].…”
Section: Ac Field Techniquementioning
confidence: 99%